ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Rosna K. Harahap; Dwi Mradipta Jiwana (Media Riset Akuntansi, Auditing & Informasi, 2009)
The objective of this research is to know whether inventory variability, company size, Leverage, gross profit margin, current ratio, inventory intensity and cost of goods sold variability are factors that influence the choice of inventory accounting method in manufacturing companies listed at Jakarta Stock Exchange. The samples are 36 listed manufactured company at Jakarta Stock Exchange during 2002-2006 which selected using purposive non random sampling. Data analyzed methods used are univariate test using Mann Whitney and t-test and multivariate test using logistic regression method. The result of univariate test is that inventory variability, company size, Leverage, current ratio, inventory intensity and cost of goods sold variability of companies using FIFO method differ than those are from companies using average method. However, gross profit margin of companies using FIFO method is the same as the profit margin of companies using average method. The result of multivariate test shows that company size, current ratio, inventory intensity, and cost of goods sold variability influence the choice of inventory accounting method. In contrary, inventory variability, Leverage, and gross profit margin of companies using FIFO method have no influence to companies using average method.Keywords: Inventory Method, Inventory Variability, Company Size, Leverage, Gross Profit Margin, Current Ratio, Inventory Intensity, Cost of Goods Sold Variability.